Long-Term Follow-Up of Nonoperatively and Operatively Treated Acute Primary Patellar Dislocation in Skeletally Immature Patients - Eva Bengtsson Moström; Christina Mikkelsen; Lars Weidenhielm; Per-Mats Janarv (The Scientific World Journal)
Purpose. The present study reports a long-term follow-up of acute primary patellar dislocation in patients with open physes. The purpose of the study was to evaluate knee function and recurrence rates after surgical and nonsurgical treatment of patellar dislocation. Methods. A total of 51 patients, including 29 girls and 22 boys, who were 9–14 years of age at the time of injury, were retrospectively evaluated. The minimum follow-up time was 5 years. Thigh muscle torque, range of motion, the squat test, the knee injury and osteoarthritis outcome score (KOOS), the Kujala score, and the recurrence rate were registered. Radiological predisposing factors at the time of injury were determined. Results. Quality of life and sports/recreation were the most affected subscales, according to KOOS, and a reduced Kujala score was also observed in all treatment groups. The surgically treated patients had a significantly lower recurrence rate. Those patients also exhibited reduced muscle performance, with a hamstring to quadriceps ratio (H/Q) of 1.03. The recurrence rate was not correlated with knee function. Conclusions. Patellar dislocation in children influences subjective knee function in the long term. Surgery appears to reduce the recurrence rate, but subjective knee function was not restored.